Design and Demonstration of MOCVD-Grown p-Type AlxGa1-xN/GaN Quantum Well Infrared Photodetector - Alireza Lanjani; Benjamin McEwen; Vincent Meyers; David Hill; Winston K. Chan; Emma Rocco; Shadi Omranpour; F. Shahedipour-Sandvik (IEEE Photonics Journal, 2024)
Quantum well infrared photodetectors (QWIPs) have been demonstrated to be a suitable candidate for IR detection applications. These detectors attracted increasing interest due to their design flexibility and broad spectral absorption from short wave (SWIR) to long wave infrared (LWIR) and high uniformity. In this paper, we demonstrate device design, growth, and characterization of a p-type AlxGa1-xN/GaN quantum well infrared photodetector (QWIP) for near IR absorption with 1.55 μm peak grown by metal organic chemical vapor deposition (MOCVD). Utilizing a p-QWIP allows for normal incidence light absorption due to the strong band mixing between heavy and light holes at k ≠ 0 which eliminates the need for light couplers such as grating and facilitates the fabrication of large focal plane arrays (FPAs). We developed MOCVD growth conditions to achieve nm-thick and smooth interfaces in QWIP. Sample characterizations including atomic force microscopy (AFM) show uniform surface morphology with RMS roughness ∼0.5 nm. Scanning transmission electron microscopy (STEM) was used to characterize layer thicknesses and interface roughness. We demonstrate energy band diagram simulation of an AlxGa1-xN/GaN p-QWIP by considering polarization chargers to determine the accurate band offset and adjust the absorption wavelength (ISBT energies). Our results show the feasibility of MOCVD-grown p-type AlxGa1-xN/GaN QWIP for IR absorption and open a pathway for further research and growth development on III-Nitride p-QWIPs, allowing growth and fabrication of large focal plane arrays.